The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/en13071817
|View full text |Cite
|
Sign up to set email alerts
|

Energy Recovery from Waste Tires Using Pyrolysis: Palestine as Case of Study

Abstract: The first industrial-scale pyrolysis plant for solid tire wastes has been installed in Jenin, northern of the West Bank in Palestine, to dispose of the enormous solid tire wastes in the north of West Bank. The disposable process is an environmentally friendly process and it converts tires into useful products, which could reduce the fuel crisis in Palestine. The gravimetric analysis of tire waste pyrolysis products from the pyrolysis plant working at the optimum conditions is: tire pyrolysis oil (TPO): 45%, py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 31 publications
(22 reference statements)
0
22
0
Order By: Relevance
“…In addition to these, Zhang et al ( 2019 ) analyzed using carbon from ELT pyrolysis for wastewater treatment. Abdallah et al ( 2020 ) found that the produced pyrolysis oil could replace conventional liquid fuels. Buadit et al ( 2020 ) evaluated the potential environmental impacts of an ELT pyrolysis plant in Thailand by using the LCA method.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to these, Zhang et al ( 2019 ) analyzed using carbon from ELT pyrolysis for wastewater treatment. Abdallah et al ( 2020 ) found that the produced pyrolysis oil could replace conventional liquid fuels. Buadit et al ( 2020 ) evaluated the potential environmental impacts of an ELT pyrolysis plant in Thailand by using the LCA method.…”
Section: Resultsmentioning
confidence: 99%
“…Green energy refers to renewable energy sources that are regarded to be environmentally friendly. These energy sources aid in mitigating the consequences of global warming, a rise in the Earth's average temperature caused by fossil fuel emissions [1][2][3]. The construction industry is well-known as one of the world's largest energy users [4].…”
Section: Introductionmentioning
confidence: 99%
“…Pyrolysis process is based on a thermochemical decomposition of the organic biomass after heating it up to 400 to 550 • C with no presence of oxygen producing bio-oil, char, and synthesis gas [21]. The produced Bio-oil, which is a condensed vapor of mixture of organic chemicals with water, can be a vital fuel alternative in many static applications like boiler and diesel engines for power generations in the refugee camps [22]. Household food waste provides zero cost feedstock for various chemicals and energy production while solving the management burden [23].…”
Section: Introductionmentioning
confidence: 99%
“…The pyrolysis and co-pyrolysis of mixture of wastes have drawn a wide awareness in current years [26]. However, proper selection of sustainable input materials and process conditions optimization are the significant prerequisite for their successful application [22,27,28].…”
Section: Introductionmentioning
confidence: 99%